Provenance of late Pleistocene loess in central and eastern Europe: isotopic evidence for dominant local sediment sources - K. Fenn; I. L. Millar; A. Bird; D. Veres; Doris Wagner (Scientific Reports)
Abstract Loess profiles along the Danube River provide a record of long-term Quaternary dust (loess) deposition in central-eastern Europe. Here, Sr–Nd isotopic data from four loess-palaeosol profiles (47 samples) spanning the last two-glacial-interglacial cycles are presented. The isotopic compositions generated by this study are compared with bedrock and sedimentary samples from Europe and North Africa to decipher the sources of sediment. The results demonstrate that over the last 300 ka the alluvial plains of the Danube (which are themselves sourced from surrounding mountain belts) are a local source of material and consequently sediment experiences aeolian transport over relatively short distances. The results dispute the commonly held assumption that the Sahara was a sediment contributor to loess in central-eastern Europe as North African contributions are not needed to explain loess signatures. Consequently, the findings suggest a suppressed southerly wind direction and dominance of the westerly and north-westerly wind systems over the entirety of the record.